Assessment of Psycho-social factors associated with Relapses among Mental Patients. A Cross-sectional study at Mbale Regional Referral Hospital. - Michael Kabasa (Student's Journal of Health Research, 2022)
Background:  WHO (1996) estimated that 12.5% of the global burden of disease is caused by mental and neurological disorders. In a few studies carried out in Uganda mental illnesses seem to claim a big share of medical costs because of relapses. Objectives:  The major objective was to assess Psycho-social factors associated with relapses among Mental patients and reduce readmission at the Psychiatric ward, Mbale Regional Referral Hospital. The specific objectives were: to identify demographic characteristics of relapsed mental patients and to determine psychological and social factors associated with relapses among mental patients. Methodology:  A descriptive cross-sectional design was employed to target all mentally relapses patients who had improved using consecutive sampling on a sample of 168 respondents. Data were collected using structured questionnaires and analyzed using spss18 software and manually, presented in frequency tables and charts. Data were managed by storage in hard copies and electronically under lock and key. Results:  The study findings revealed that females (51.2%) of young aged 15-24 years had more mental relapses. Most respondents had attained secondary education (41.7%) with many peasants (33.6%) staying single (53.0%). The commonest mental disorder was bipolar mania (25.6%). The majority also accepted that psychologically they had improved (57.1%) with highly expressed emotions and socially medicines were expensive (78.6%). Conclusion:  Mental illnesses start early in life, and incapacitate patients through relapses but psychosocial factors can be importantly considered to remedy their plight.  Recommendations: Health care providers should strengthen the health education given to mental patients and their caretakers to reduce the vice of relapses. The government put up ring funding to community health programs to improve school mental health important in the prevention of mental disorders.